2020
DOI: 10.1002/cam4.3560
|View full text |Cite
|
Sign up to set email alerts
|

The role of surgery on the primary tumor site in bladder cancer with distant metastasis: significance of histology type and metastatic pattern

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 23 publications
3
12
0
Order By: Relevance
“…In our stable visualized nomogram, histology, differentiation, chemotherapy, T stage, and age were primary predictive variables that could estimate whether an mBC patient could benefit from the removal of the primary tumor. Our research is in line with the recent study that histology type is an independent prognostic factor for OS ( 22 ). According to our study, patients with non-urothelial carcinoma have a greater chance of benefiting from PTR.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our stable visualized nomogram, histology, differentiation, chemotherapy, T stage, and age were primary predictive variables that could estimate whether an mBC patient could benefit from the removal of the primary tumor. Our research is in line with the recent study that histology type is an independent prognostic factor for OS ( 22 ). According to our study, patients with non-urothelial carcinoma have a greater chance of benefiting from PTR.…”
Section: Discussionsupporting
confidence: 92%
“…For mBC undergoing chemotherapy, PTR still can prolong survival time. Similar to this finding, a study confirmed that both surgery and chemotherapy are independent prognostic risk factors ( 22 ). The PTR combined with multimodality therapy could prolong survival time ( 24 ).…”
Section: Discussionsupporting
confidence: 79%
“…The development of skeletal disease is associated with impaired QoL because of severe complications such as pain, pathological fractures, nerve root or spinal cord or compression, reduced mobility, and hypercalcemia (43). Since the pathophysiology and formation mechanism of bone metastases is rather complex, involving several events at the primary site as well as the metastatic sites, a multidisciplinary approach is needed to manage metastatic skeletal disease, including treatment modalities such as surgery, chemotherapy, RT, bisphosphonates, and radioisotopes (44)(45)(46).…”
Section: Radiotherapy For Bone Metastasesmentioning
confidence: 99%
“…Surgical resection of the primary tumor is a crucial component of the complex remedy of many metastatic tumors [ 23 , 24 ]. Nevertheless, only a few researches have assessed the impact of surgery on survival outcomes in bladder cancer with organ metastasis [ 25 , 26 ]. Moreover, only a few researches have evaluated the impact of surgery on survival outcomes of UBUC patients with organ metastasis.…”
Section: Discussionmentioning
confidence: 99%